Risk factors of neuropathic pain after thoracic surgery - Homma, Takahiro (J Thorac Dis, 2018)
BACKGROUND: This study aimed to clarify the incidence and risk factors of neuropathic pain after thoracic surgery, focusing especially on patients who underwent complete video-assisted thoracoscopic surgery (VATS). METHODS: We retrospectively identified 185 patients who underwent thoracic surgery at our hospital over a 2-year period. Logistic regression analysis was used to analyze the association of various factors with postoperative neuropathic pain. RESULTS: Forty-eight (25.9%) patients developed postoperative neuropathic pain, and 9 (18.8%) of these patients reported persistent pain 1 year postoperatively. The median interval from surgical treatment to the onset of neuropathic pain was 7 days, and the duration was 50 days. Multivariate logistic regression analysis revealed a significant positive correlation between postoperative neuropathic pain and preoperative use of hypnotic medication [odds ratio (OR), 5.45; 95% confidence interval (CI); 2.52–12.17] and duration of surgery ≥2.5 hours (OR, 2.72; 95% CI, 1.27–6.09), and a significant negative association with the complete VATS approach (OR, 0.18; 95% CI, 0.073–0.42). CONCLUSIONS: Preoperative use of hypnotic medication, the thoracotomy approach, and duration of surgery ≥2.5 hours are associated with increased risk of neuropathic pain after thoracic surgery. The complete VATS approach could decrease the incidence of postoperative neuropathic pain, regardless of the duration of surgery.